2019
DOI: 10.1557/jmr.2019.122
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of anti-solvent engineering toward high performance perovskite solar cells

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Numerous efforts have already been dedicated to obtain high quality perovskite films with dense surface and large grain size through the utilization of green antisolvents such as ethanol (Eth), isopropanol, and ether. [13,14] Unfortunately, most of these cases have compromised device performance. [13,14] For example, Ethtreated PSCs typically exhibit a low efficiency, which is due to two reasons: 1) Eth partly decomposes the perovskite that leads into the formation of uneven and unfully covered perovskite film with defects; [14] 2) Some defects on the surface of perovskite due to relatively high polarity and low boiling point of Eth, which seriously impacts the nucleation kinetics and crystal growth.…”
Section: Doi: 101002/adma202003965mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous efforts have already been dedicated to obtain high quality perovskite films with dense surface and large grain size through the utilization of green antisolvents such as ethanol (Eth), isopropanol, and ether. [13,14] Unfortunately, most of these cases have compromised device performance. [13,14] For example, Ethtreated PSCs typically exhibit a low efficiency, which is due to two reasons: 1) Eth partly decomposes the perovskite that leads into the formation of uneven and unfully covered perovskite film with defects; [14] 2) Some defects on the surface of perovskite due to relatively high polarity and low boiling point of Eth, which seriously impacts the nucleation kinetics and crystal growth.…”
Section: Doi: 101002/adma202003965mentioning
confidence: 99%
“…[13,14] Unfortunately, most of these cases have compromised device performance. [13,14] For example, Ethtreated PSCs typically exhibit a low efficiency, which is due to two reasons: 1) Eth partly decomposes the perovskite that leads into the formation of uneven and unfully covered perovskite film with defects; [14] 2) Some defects on the surface of perovskite due to relatively high polarity and low boiling point of Eth, which seriously impacts the nucleation kinetics and crystal growth. [13] From previous studies, it is known that defectsinduced nonradiative recombination is the predominant recombination that degrades the solution pro cessed PSCs performance.…”
Section: Doi: 101002/adma202003965mentioning
confidence: 99%
“…13,22 Antisolvents which improve film formation often exhibit low polarity and dielectric constants, high boiling points, good miscibility with the precursor solvent, and cannot dissolve any perovskite or related precursor phase. 8,23,24 The most commonly used antisolvents are toluene 13 , chlorobenzene 22 , and diethyl ether, 24 but many others have been tested as well. 21,22,[24][25][26] The aim of the antisolvent is to accelerate the crystallization process, induce homogeneous nucleation with high nucleation density, thus promote uniform grain growth leading to significantly improved morphology, surface coverage, and formation of larger grains.…”
Section: Introductionmentioning
confidence: 99%
“…However, abnormal hysteresis, poor long-term stability in air and light, high lead toxicity, and surface/interface issues prevent their entry into the photovoltaic device market [4][5][6]. The key to improve PCE of hybrid perovskite solar cell is to optimize the morphology of perovskite layer as light absorption, charge transport, and carrier recombination depend on film morphology [1][2][3][4][5][6][7][8][9]. Thus different fabrication methods like one-step spin coating, two-step sequential deposition, evaporation, vapor, and additive assisted deposition, spray pyrolysis, doctor blade method etc.…”
Section: Introductionmentioning
confidence: 99%
“…were developed. Recently it was observed that antisolvent method became popular to optimize morphology and improve PCE of hybrid perovskite solar cells [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%